A two-stage Islamophobia: The American Muslim Image between Integration and public ‘estrangement’ in Chapel Hill reporting - Boulahnane, Saad (Journal of Humanities & Social Sciences, 2018)
This article is a critical investigation of American mainstream news media’s reporting of Chapel Hill shooting, which is characterized by being double-biased. The two-stage Islamophobia, or double-biased anti-Muslim reporting, was a result of mainstream media’s incessant endeavor to discursively frame the anti-Muslim crime into a ‘run-of-the-mill’ incident. Media’s concerted efforts in both veiling the Islam phobic character of the crime and reinterpreting it into one that is not hate driven resulted in what is labeled in this article as two-stage Islamophobia, which is double-biased anti-Muslim reporting. Informed by framing theory, this study adopts content analysis, qualitative and quantitative, to identify the recurring themes constituting the general frame. The data were retrieved from LexisNexis, an academic database, and analyzed using qualitative data mining program, Atlas.ti, The study has resulted in American mainstream news media, particularly CNN and Fox News, engaging in a two-stage Islamophobia. It is characterized by the (n=0) Fox News broadcast transcripts, which rendered invisible the American Muslims in the American public space, hence a total underrepresentation. The American Muslims were also misrepresented in CNN’s biased coverage, in which they were reduced into the ‘other’ in a superposed un-Islamophobic crime. The findings relate to the literature on the relationship between American mainstream media and the status and identity of American Muslims, particularly in the context of religious pluralism.